Tight Coupling of Glaciecola spp. and Diatoms during Cold-Water Phytoplankton Spring Blooms - von Scheibner, Markus; Sommer, Ulrich; Jürgens, Klaus (Frontiers in Microbiology, 2017)
Early spring phytoplankton blooms can occur at very low water temperatures but they are often decoupled from bacterial growth, which is assumed to be often temperature controlled. In a previous mesocosm study with Baltic Sea plankton communities, an early diatom bloom was associated with a high relative abundance of Glaciecola sequences (Gammaproteobacteria), at both low (2°C) and elevated (8°C) temperatures, suggesting an important role for this genus in phytoplankton-bacteria coupling. In this study, the temperature-dependent dynamics of free-living Glaciecola spp. during the bloom were analyzed by catalyzed reporter deposition fluorescence in situ hybridization using a newly developed probe. The analysis revealed the appearance of Glaciecola spp. in this and in previous spring mesocosm experiments as the dominating bacterial clade during diatom blooms, with a close coupling between the population dynamics of Glaciecola and phytoplankton development. Although elevated temperature resulted in a higher abundance and a higher net growth rate of Glaciecola spp. (Q10 ∼ 2.2), their growth was, in contrast to that of the bulk bacterial assemblages, not suppressed at 2°C and showed a similar pattern at 8°C. Independent of temperature, the highest abundance of Glaciecola spp. (24.0 ± 10.0% of total cell number) occurred during the peak of the phytoplankton bloom. Together with the slightly larger cell size of Glaciecola, this resulted in a ∼30% contribution of Glaciecola to total bacterial biomass. Overall, the results of this and previous studies suggest that Glaciecola has an ecological niche during early diatom blooms at low temperatures, when it becomes a dominant consumer of phytoplankton-derived dissolved organic matter.